Method for rapidly preparing high-strength and high-compactness quartz fiber reinforced quartz-based composite material
By using vacuum or inert atmosphere to perform interface pretreatment in the preparation process of quartz fiber-reinforced quartz ceramic matrix composite materials, combined with continuous heating, low-pressure boiling impregnation-in-situ gel curing-low-pressure drying, the problems of complex processes, long cycles and insufficient product density in the prior art are solved, and efficient and simplified preparation processes and high-performance composite materials are achieved.
Patent Information
- Application Number
- CN202510094592.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-21
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2045-01-21
AI Technical Summary
In the prior art, when preparing quartz fiber reinforced quartz ceramic matrix composites, the process flow is complex, the preparation period is long, and the stability of high-concentration silicon sols is poor, resulting in insufficient product density and consistency, making it difficult to achieve industrial production.
Interface pretreatment is carried out using vacuum or inert atmosphere to form a carbon-containing interface layer to weaken the strong interface bond between the fiber and the matrix. Then, by continuously heating the low-pressure boiling impregnation-in-situ gel curing-low-pressure drying process, the impregnation and drying equipment and process flow are simplified and the preparation cycle is shortened.
It significantly shortens the preparation cycle, simplifies the process flow, reduces manufacturing costs, improves the density and mechanical properties of composite materials, and is suitable for industrial production.
Smart Images

Figure CN119874397A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of preparation of high-temperature resistant and wave-transmitting quartz fiber reinforced quartz-based composite materials, and in particular to a method for rapidly preparing high-strength and high-density quartz fiber reinforced quartz-based composite materials. Background Art
[0002] Quartz fiber reinforced quartz ceramic matrix composite materials have excellent comprehensive mechanical, thermal and electrical properties. They are currently the most mature and widely used ceramic matrix wave-transparent composite materials at home and abroad. The radome / antenna window products made of this material have been widely used in the aerospace wave-transparent field.
[0003] At present, the methods for preparing quartz fiber reinforced quartz ceramic matrix composite materials mainly include sol-gel method (Sol-gel), liquid phase infiltration method (or liquid phase impregnation method) and chemical vapor infiltration method (CVI), among which the most widely used is sol-gel method. Its process is: mainly using silica sol to impregnate quartz fiber preform, after multiple impregnation-drying gel-sintering cycles, a certain density of the initial blank component is obtained, and then it is processed, moisture-proof and coated to obtain the final product. Due to the low stability of high-concentration silica sol, low-concentration silica sol is used more in this process, and it is necessary to repeatedly cycle impregnation and drying. With the increase of the impregnation cycle, there is often an obvious density gradient difference between the surface layer and the core layer of the product. The high surface density leads to low efficiency of the later impregnation, and it needs to be repeatedly processed before impregnation. The product preparation process is complicated and the preparation cycle is long. Therefore, people explore new processes and methods through various optimization methods to quickly prepare high-density and uniform quartz fiber reinforced quartz ceramic matrix composite materials.
[0004] Silica sol impregnation is a key process for densification of quartz fiber reinforced quartz-based composite materials. Commonly used impregnation methods include vacuum impregnation and high-pressure impregnation, both of which penetrate silica sol into the pores of quartz fibers or blanks through pressure difference. Chinese patent publication number CN 113896554 A discloses a vacuum impregnation process using silica slurry and silica sol in combination to achieve the preparation of high-density fiber reinforced quartz ceramic composite materials. However, the silica slurry in the preparation process is a high-concentration suspension slurry with low stability and needs to be prepared and used immediately. The two impregnation processes require repeated impregnation and sintering for multiple times, which causes great damage to the fibers and fails to fundamentally solve the structure of the matrix material that is dense on the outside and sparse on the inside. The resulting product has low consistency and is not conducive to industrial production. The Chinese patent publication number CN 113511879 A discloses a silica sol gradient impregnation method for quartz fiber preforms of "high concentration-medium concentration-low concentration". Different densification cycles are designed to use a combination of silica sols of different concentrations for impregnation, which improves the impregnation efficiency and shortens the preparation cycle of quartz fiber reinforced quartz-based composite materials. However, before impregnation, the commercially available acidic silica sol needs to be concentrated by reduced pressure rotary evaporation, which increases the number of processes and the cost. Chinese patent 103601479A discloses a method for preparing a high-temperature resistant ultra-thin antenna window. First, the preform is preformed by pressurization, and then 55% to 65% silica sol, 38% to 40% silica sol, 30% silica sol, SAR-9 silicone resin and 30% silica sol are used in sequence for impregnation-drying gel-sintering. The gradient concentration silica sol impregnation process is used to reduce the number of impregnation times and shorten the preparation cycle. However, the high concentration silica sol in this process also has stability problems, and silicone resin needs to be impregnated in this process to increase stiffness. If the silicone resin is not completely sintered, it will affect the wave transmission performance of the composite material.
[0005] There are three common methods for drying and curing silica sol: curing in air, curing in colloid and rapid gel curing. Chinese patent publication number CN105272119A discloses in-situ gel curing of silica sol by adding ammonia to avoid overflow and loss of silica sol, and then using microwave drying technology to improve drying efficiency. However, this process requires the use of pungent odor gas and microwave drying rotating equipment, and needs to be recycled about 20 times, so the preparation process is relatively complicated. Chinese patent publication number CN117700251A discloses that a preform is repeatedly impregnated with a low-density silica sol under vacuum conditions, and then a radome product with a relatively uniform density is prepared by combining a rotary drying method. Although vacuum conditions are more conducive to the silica sol to uniformly penetrate into the internal pores of the fiber, the rotary drying method avoids the problem of crusting on the surface of the blank and eliminates the rough machining process during the product impregnation process, the total impregnation cycle exceeds 10 rounds and each round of impregnation time exceeds 20 hours, and the process cycle is too long; therefore, how to use commercially available low-concentration silica sol with high stability under relatively simple equipment conditions to quickly prepare high-strength, high-density and uniform quartz fiber reinforced quartz ceramic-based composite materials and stably realize the industrial production of the products is still a difficulty that needs to be urgently solved. Summary of the invention
[0006] In view of the above shortcomings, the present invention provides a method for quickly preparing a high-strength and high-density quartz fiber reinforced quartz-based composite material, which can significantly shorten the preparation cycle, simplify the impregnation and drying equipment and process flow, reduce the manufacturing cost, and is conducive to industrial production. The prepared quartz fiber reinforced quartz-based composite material has high density, small density gradient, and high strength. The specific technical scheme is as follows:
[0007] A method for rapidly preparing a high-strength and high-density quartz fiber reinforced quartz-based composite material comprises the following steps:
[0008] (1) placing a quartz fiber preform that has been interface pretreated in a vacuum or inert atmosphere into a vacuum impregnation tank, adding silica sol to ensure that the preform is completely immersed, and sealing the impregnation tank;
[0009] (2) The impregnation tank is subjected to low-pressure heating and boiling impregnation, so that the silica sol is kept in a violent boiling state at low pressure and low temperature (the gas pressure in the tank is reduced, and the boiling point of the aqueous solution is correspondingly reduced), and low-pressure boiling impregnation is performed. After a period of impregnation, the heating temperature is increased to perform in-situ gel curing of the silica sol, and low-pressure drying is performed. The whole process is continuously maintained at a low pressure state to obtain a preform; by continuous low pressure and heating, the air inside the preform is completely evacuated to ensure that the silica sol fully infiltrates the inside of the preform, so that the silica sol is kept in a violent boiling state, the volatilized water vapor is evacuated, the silica sol is continuously concentrated, and high-concentration silica sol impregnation is simultaneously achieved;
[0010] (3) taking out the preform and cleaning the surface gel, and repeating the low-pressure boiling impregnation-in-situ gel curing-low-pressure drying process of step (2) for several times, successively shortening the low-pressure boiling impregnation time during the cyclic impregnation process, thereby concentrating silica sols of different concentrations during the impregnation process, and realizing in-situ impregnation of silica sols of different gradient concentrations;
[0011] (4) Sintering the blank to obtain a high-strength and high-density quartz fiber reinforced quartz matrix composite material.
[0012] Preferably, in the above-mentioned method for rapidly preparing high-strength and high-density quartz fiber reinforced quartz-based composite materials, in the step (1), the interface pretreatment temperature of the quartz fiber preform is 400°C to 650°C, the heating rate is 1°C / min to 20°C / min, the holding time is 60min to 360min, and the atmosphere during the pretreatment process is vacuum, nitrogen, helium or argon. By cracking the impregnating agent resin on the surface of the preform fiber in a vacuum or inert atmosphere, the interface layer of the carbon-containing coating is obtained on the surface of the quartz fiber, the dehydration condensation effect of the hydroxyl groups on the surface of the quartz fiber and the surface of the silica gel group during the silica sol impregnation process is reduced, and the strong interface bonding between the fiber and the matrix is weakened, so that when the material is damaged, the cracks caused by the shrinkage of the matrix will not penetrate the fiber due to the strong interface bonding, resulting in the overall brittle fracture of the material, which protects the quartz fiber, is conducive to the strengthening and toughening effect of the reinforcing fiber, and improves the mechanical properties of the composite material.
[0013] Preferably, in the above-mentioned method for rapidly preparing a high-strength and high-density quartz fiber reinforced quartz-based composite material, in the step (1), the interface pretreatment temperature of the quartz fiber preform is 500°C to 550°C, the heating rate is 5°C / min to 10°C / min, the insulation time is 90min to 180min, and the atmosphere during the pretreatment process is vacuum or nitrogen.
[0014] Preferably, in the above-mentioned method for rapidly preparing a high-strength and high-density quartz fiber reinforced quartz-based composite material, in the step (1), the impregnation tank is a contoured impregnation tank, which is contoured according to the outer dimensions of the fabric to reduce the amount of silica sol used. After the silica sol is added, the silica sol liquid level is 10 mm to 80 mm higher than the top of the preform, ensuring that during the continuous heating and low-pressure boiling impregnation process, the preform is still immersed in the solution after the silica sol volume is concentrated and reduced.
[0015] Preferably, in the above method for rapidly preparing a high-strength and high-density quartz fiber reinforced quartz-based composite material, in step (1), after adding the silica sol, the silica sol liquid level is 30 mm to 50 mm higher than the top of the preform.
[0016] Preferably, in the above-mentioned method for rapidly preparing high-strength and high-density quartz fiber reinforced quartz-based composite materials, the silica sol is a commercially available high-purity stable acidic silica sol with a solid content of 20wt.% to 30wt.%, a viscosity of less than 15mpa·s, a pH of 2 to 4, and a particle size of SiO2 micelles in the silica sol of 5nm to 100nm.
[0017] Preferably, in the above-mentioned method for rapidly preparing high-strength and high-density quartz fiber reinforced quartz-based composite materials, in the step (2), the air pressure in the tank is maintained at 500Pa to 1500Pa throughout the process, the low-pressure boiling impregnation temperature is 5°C to 35°C, the impregnation time is 0.5h to 3h, and the heating temperature is gradually increased during the in-situ gel curing and low-pressure drying process, the temperature range is 70°C to 250°C, and the gel curing time and low-pressure drying time are both 1h to 4h. Under continuous heating and low pressure conditions, the silica sol is easy to gel when the temperature is higher than 35°C, so the temperature is ensured to be 5°C to 35°C during the impregnation process to prevent the silica sol from gelling too quickly, which is not conducive to the complete penetration of the preform.
[0018] Further, preferably, in the above-mentioned method for rapidly preparing a high-strength and high-density quartz fiber reinforced quartz-based composite material, in the step (2), the air pressure in the tank is maintained at 500Pa to 1000Pa throughout the entire process, the low-pressure boiling impregnation temperature is 15°C to 35°C, and the heating temperature is gradually increased during the in-situ gel curing and low-pressure drying process, and the temperature range is 80°C to 200°C.
[0019] Preferably, in the above-mentioned method for rapidly preparing a high-strength and high-density quartz fiber reinforced quartz-based composite material, in the step (3), the low-pressure boiling impregnation-in-situ gel curing-low-pressure drying is circulated 1 to 6 times, the low-pressure boiling impregnation time decreases successively from the first impregnation time, and the in-situ gel curing and drying process system is the same as that of step (2).
[0020] Preferably, in the above-mentioned method for rapidly preparing a high-strength and high-density quartz fiber reinforced quartz-based composite material, in the step (3), the low-pressure boiling impregnation-in-situ gel curing-low-pressure drying is cycled 2 to 4 times.
[0021] Preferably, in the above method for rapidly preparing a high-strength and high-density quartz fiber reinforced quartz-based composite material,
[0022] Preferably, in the above method for rapidly preparing a high-strength and high-density quartz fiber reinforced quartz-based composite material, the cyclic low-pressure boiling impregnation time is successively reduced by 0.2 to 1 h.
[0023] Preferably, in the above method for rapidly preparing a high-strength and high-density quartz fiber reinforced quartz-based composite material, the cyclic low-pressure boiling impregnation time is successively reduced by 0.5 to 1 hour.
[0024] Preferably, in the above-mentioned method for rapidly preparing a high-strength and high-density quartz fiber reinforced quartz-based composite material, in the step (4), sintering is carried out in the air of a muffle furnace, the sintering temperature is 700°C to 900°C, the heating rate is 1°C / min to 10°C / min, and the holding time is 30min to 360min. The sintering process has the effect of oxidizing and decomposing the carbon coating on the surface of the quartz fiber, and at the same time sintering and densifying the preform and the matrix to a certain extent.
[0025] Preferably, in the above-mentioned method for rapidly preparing a high-strength and high-density quartz fiber reinforced quartz-based composite material, in the step (4), the sintering is carried out in the air of a muffle furnace, the sintering temperature is 750°C to 800°C, the heating rate is 1°C / min to 3°C / min, and the holding time is 90min to 180min.
[0026] On the other hand, the present invention also provides a high-strength and high-density quartz fiber reinforced quartz-based composite material, which is prepared by the above method.
[0027] Compared with the prior art, the present invention has the following beneficial effects:
[0028] 1. The method for rapidly preparing high-strength and high-density quartz fiber reinforced quartz-based composite materials of the present invention is to sinter the quartz fiber surface by vacuum or inert atmosphere pretreatment, so that the infiltrant on the quartz fiber surface is cracked in situ to obtain a carbon-containing interface layer, which prevents the quartz fiber surface hydroxyl and the silica sol surface hydroxyl from dehydrating and condensing to form a strong interface bond during the impregnation-gel-drying process, and then sinter the carbon-containing interface layer by oxidation and burning in the air muffle furnace in the later stage, so that the porous structure is formed in situ between the fiber and the matrix, and the strong interface bond between the fiber and the matrix is further weakened, and the cracks generated by the matrix shrinkage when the material is damaged will not penetrate the fiber due to the strong interface bond, resulting in brittle fracture of the whole material. The carbon coating obtained by the interface treatment does not affect the dielectric wave transmission of the composite material, and effectively protects the fiber during the high-temperature sintering process, and the entire composite material preparation process is sintered only once, which reduces the thermal damage to the quartz fiber during multiple sintering processes, so that the quartz fiber effectively plays a role of toughening and strengthening, and improves the mechanical properties of the composite material.
[0029] 2. In the method for rapidly preparing high-strength and high-density quartz fiber reinforced quartz-based composite materials of the present invention, by continuously heating low-pressure boiling impregnation, the silica sol can continue to maintain a boiling and evaporating state at a low pressure and a low temperature (the air pressure is reduced, and the boiling point of the aqueous solution is correspondingly reduced), so that the air in the pores of the quartz fiber preform is continuously discharged to fill the silica sol, and the concentration of the silica sol is continuously concentrated, so that the impregnation and concentration of the silica sol are carried out simultaneously, and by controlling the impregnation heating temperature within 35°C, the silica sol is prevented from gelling quickly to affect the impregnation efficiency. In addition, in the subsequent cyclic impregnation process, by shortening the time of low-pressure boiling impregnation, a silica sol with decreasing concentration can be obtained at the end of the impregnation by using a commercially available low-concentration silica sol with high stability, and the in-situ gradient concentration impregnation can further improve the impregnation efficiency, solve the defect of poor storage stability of high-concentration silica sol, and there is no need to obtain silica sols of different concentrations through the early decompression process, simplifying the process, and facilitating industrial production.
[0030] 3. In the present invention, the process of continuous heating low-pressure boiling impregnation-in-situ gel curing-low-pressure drying is adopted. Continuous heating low-pressure boiling impregnation can improve the thermal motion and concentration of silica sol molecules while impregnating, thereby improving the impregnation efficiency: if only continuous low-pressure impregnation is performed without heating the silica sol, water evaporation is an endothermic reaction, resulting in the silica sol temperature becoming lower and lower, and the molecular thermal motion becoming slower and slower, which is not conducive to impregnation. In-situ gel curing guarantees the uniform distribution of silica sol in the preform to the greatest extent, and avoids the defect of water molecules driving silica sol molecules to accumulate from the inside to the outside on the fabric surface during the volatilization process to form a dense outer and sparse inner defect. Continuous heating and vacuum drying are conducive to the formation of open-pore channels for the volatilization of water molecules, which can not only accelerate the evaporation of water and the drying process, but also reduce the surface closed pores, which is beneficial to the next impregnation, reduce the number of impregnations, shorten the impregnation cycle, and further improve the impregnation efficiency. At the same time, this process realizes the integration of the entire process of vacuum impregnation-in-situ gel curing-drying. The vacuum impregnation, in-situ gel curing and vacuum drying processes are continuously integrated with the same equipment, which greatly simplifies the process equipment, reduces the process operation flow and reduces production costs.
[0031] 4. The quartz fiber reinforced quartz-based composite material prepared by the present invention has a uniform matrix distribution, a small density gradient, a high density, a high strength, and a strong designability. The number of cyclic impregnation times can be selected as needed. The production equipment is simple. The silica sol used is a low-concentration commercially available silica sol with good stability, a long storage period, low raw material cost, and a safe process. It is conducive to large-scale industrial production and can be applied to the field of high-temperature resistant and wave-transparent materials in aerospace. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are some embodiments of the present invention, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0033] Figure 1 Schematic diagram of the structure of the continuous vacuum impregnation-in-situ gel curing-drying equipment.
[0034] Legend: 1- impregnation tank, 2- vacuum pump, 3- silica sol, 4- heating body, 5- preform. DETAILED DESCRIPTION
[0035] The specific embodiments of the present invention are described in detail below, but it should be understood that the protection scope of the present invention is not limited by the specific embodiments. Unless otherwise defined, all professional terms used hereinafter have the same meaning as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the protection scope of the present invention. Unless otherwise specifically stated, various raw materials, reagents, instruments and equipment used in the present invention, etc. can be purchased from the market or can be prepared by existing methods.
[0036] The silica sol in the following examples and comparative examples is an aqueous solution containing SiO2 nanoparticles, purchased from Hebei Jiashi Hongwei Technology Co., Ltd., and the quartz fiber preform is purchased from Hubei Feilihua Quartz Glass Co., Ltd.
[0037] Example 1
[0038] A method for rapidly preparing a high-strength and high-density quartz fiber reinforced quartz-based composite material comprises the following steps:
[0039] (1) A hollow cylindrical rotating body quartz fiber preform with an outer diameter of 300 mm, a height of 120 mm, and a wall thickness of 12 mm is heated to 550° C. in a vacuum furnace at a heating rate of 8° C. / min and kept at this temperature for 120 min for interface pretreatment. After the treatment, the preform is placed in a contoured impregnation tank, and silica sol is poured into the preform so that the liquid level is 50 mm above the top of the preform. The silica sol has a solid content of 25 wt.%, a viscosity of 8 mPa·s, and a particle size distribution of SiO2 nanoparticles in the silica sol of 5 nm to 60 nm. The impregnation tank is sealed;
[0040] (2) Start the vacuum pump group and the heater, and continue to heat at low pressure so that the pressure in the tank is maintained at about 700 Pa during the process of low-pressure boiling impregnation-in-situ gel curing-low-pressure drying. The temperature of the heated silica sol during impregnation is 25°C, and the silica sol is kept in a continuous boiling state during the continuous low-pressure boiling impregnation process. After impregnation for 3 hours, the heating temperature is increased to 80°C, the in-situ gel is cured for 2 hours, and finally the temperature is increased to 200°C for drying for 2 hours.
[0041] (3) After drying, the preform is taken out and the surface gel is cleaned and polished. After the heating low-pressure boiling impregnation-in-situ gel curing-low-pressure drying process in step (2) is cycled twice, the immersion time in the immersion process is reduced successively: the second immersion time is 2.5 hours, and the third immersion time is 2 hours, to obtain a preform blank, and then the blank is placed in a muffle furnace, heated to 800°C at a heating rate of 2°C / min and sintered for 120 minutes to obtain a quartz fiber reinforced quartz-based composite material.
[0042] The volume density of the prepared quartz fiber reinforced quartz matrix composite material component was calculated by volume method, and the obtained product volume density was 1.79 g / cm 3 , samples were taken from 9 different parts in the thickness direction (inside, middle and outside) and height direction (top, middle and bottom) of the component (sample size: length 80*width 10mm*thickness 5mm) to test its density and bending strength. The test results are shown in Table 1. The results show that its average density is 1.79±0.01g / cm 3 The average bending strength of the material is 102.0±3.51MPa, the bending modulus is 21.05±0.89GPa, the density gradient distribution is small, the density is uniform, and the composite material has excellent mechanical properties.
[0043] Table 1 Density and bending strength of the strips obtained by sampling and testing at different positions in Example 1
[0044]
[0045]
[0046] Comparative Example 1
[0047] The difference between this comparative example and Example 1 is that in step (2), the continuous low-pressure boiling impregnation-in-situ gel curing-low-pressure drying process is not carried out. The pressure in the tank is only reduced to 700 Pa and maintained for 30 minutes before the vacuum pump group is turned off. After the pressure is maintained at room temperature for 3 hours, the woven piece is taken out and dried in a common oven at normal pressure. The other operating conditions are the same. The specific operating steps are as follows:
[0048] (1) A hollow cylindrical rotating body quartz fiber preform with an outer diameter of 300 mm, a height of 120 mm, and a wall thickness of 12 mm is heated to 550° C. in a vacuum furnace at a heating rate of 8° C. / min and kept at this temperature for 120 min for interface pretreatment. After the treatment, the preform is placed in a contoured impregnation tank, and silica sol is poured into the preform so that the liquid level is 50 mm higher than the preform. The silica sol has a solid content of 25 wt.%, a viscosity of 8 mPa·s, and a particle size distribution of SiO2 nanoparticles in the silica sol of 5 nm to 60 nm. The impregnation tank is sealed;
[0049] (2) Start the vacuum pump group to reduce the pressure in the tank to 700Pa and keep it for 30 minutes, then turn off the vacuum pump group. After immersion at room temperature for 3 hours, restore the pressure in the tank to atmospheric pressure, take out the preform, and use a common oven to dry it at normal pressure. After drying at 80°C for 2 hours, increase the temperature to 200°C and dry it for 2 hours.
[0050] (3) After drying, the preform is taken out and the surface gel is cleaned and polished. The above operation is repeated twice to obtain a preform blank. The immersion time in the low-pressure boiling immersion process is reduced successively: the second immersion time is 2.5 h, and the third immersion time is 2 h. Subsequently, the blank is placed in a muffle furnace and heated to 800 °C at a heating rate of 2 °C / min and sintered for 120 min to obtain a composite material.
[0051] The composite material component prepared in this comparative example was characterized, and the obtained component volume density was 1.56 g / cm 3 , samples were taken from different parts of the component for density test. The results are shown in Table 2. The average density is 1.56±0.05g / cm 3 , and the corresponding average flexural strength is 56.73±8.40MPa, and the flexural modulus is 12.11±1.52GPa. Compared with Example 1, the material density of this comparative example is obviously lower, the density distribution has a gradient change, and the mechanical properties are relatively poor. This shows that the continuous heating low-pressure boiling impregnation-in-situ gel curing-low-pressure drying process has a significant effect on improving the overall density and strength of the material.
[0052] Table 2 Density and bending strength of the strips obtained by sampling and testing at different positions of Comparative Example 1
[0053]
[0054]
[0055] Comparative Example 2
[0056] The difference between this comparative example and Example 1 is that the pretreatment of the preform in step (1) is different, and the sintering is performed directly in a muffle furnace without performing atmosphere protection sintering. The other operating conditions are the same. The specific operating steps are as follows:
[0057] (1) A cylindrical rotating body quartz fiber preform with a diameter of 230 mm, a height of 120 mm, and a wall thickness of 12 mm is heated to 550° C. at a heating rate of 8° C. / min in a muffle furnace and kept at this temperature for 120 min for interface pretreatment. After the treatment, the preform is placed in a contoured impregnation tank, and silica sol is poured into the preform so that the liquid level is 50 mm higher than the preform. The silica sol has a solid content of 25 wt.%, a viscosity of 8 mPa·s, and a particle size distribution of SiO2 nanoparticles in the silica sol of 5 nm to 60 nm. The impregnation tank is sealed;
[0058] (2) Start the vacuum pump group and the heater, and continue to heat at low pressure so that the pressure in the tank is maintained at about 700 Pa during the process of heating low-pressure boiling immersion-in-situ gel curing-low-pressure drying. The temperature of the heated silica sol during immersion is 25°C. The silica sol is kept in a continuous boiling state during the continuous heating low-pressure boiling immersion process. After immersion for 3 hours, the heating temperature is increased to 80°C, the in-situ gel is cured for 2 hours, and finally the temperature is increased to 200°C for drying for 2 hours.
[0059] (3) After drying, the preform is taken out and the surface gel is cleaned and polished. After the heating low-pressure boiling impregnation-in-situ gel curing-low-pressure drying process in step (2) is cycled twice, the immersion time in the immersion process is reduced successively: the second immersion time is 2.5 hours, and the third immersion time is 2 hours, to obtain a preform blank, and then the blank is placed in a muffle furnace, heated to 800°C at a heating rate of 2°C / min and sintered for 120 minutes to obtain a quartz fiber reinforced quartz-based composite material.
[0060] The composite material component prepared in this comparative example was calculated by volume method, and the volume density of the obtained product was 1.78 g / cm 3 The density and bending strength of the components were tested by sampling from 9 different locations in the thickness direction (inside, middle and outside) and height direction (top, middle and bottom). The test results are shown in Table 3. The results show that the average density is 1.78±0.01g / cm 3 The density gradient distribution is small, which is closer to that in Example 1, but the average bending strength of the material is only 87.83±3.04MPa, and the bending modulus is 18.05±1.27GPa. The mechanical properties are significantly reduced. This shows that the preform pretreatment forms a cracked carbon coating through inert atmosphere protection, which can effectively protect the quartz fiber during the impregnation-drying-sintering process.
[0061] Table 3 Density and bending strength of the strips obtained by sampling and testing at different positions of Comparative Example 2
[0062]
[0063]
[0064] Example 2
[0065] A method for rapidly preparing a high-strength and high-density quartz fiber reinforced quartz-based composite material comprises the following steps:
[0066] (1) A cylindrical rotating body quartz fiber preform with a diameter of 300 mm, a height of 150 mm, and a wall thickness of 20 mm is heated to 480° C. at a heating rate of 5° C. / min in a nitrogen atmosphere furnace and kept at this temperature for 180 min for interface pretreatment. After the treatment, the preform is placed in a contoured impregnation tank, and silica sol is poured into the preform so that the liquid level is 40 mm higher than the preform. The silica sol has a solid content of 25 wt.%, a viscosity of 8 mPa·s, and a particle size distribution of SiO2 nanoparticles in the silica sol of 5 nm to 60 nm. The impregnation tank is sealed;
[0067] (2) Start the vacuum pump group and the heater, and continue to perform low-pressure heating to keep the pressure in the tank at about 700 Pa during the process of impregnation-in-situ gel curing-drying. The silica sol is heated to 20°C during impregnation. During the continuous heating and low-pressure process, the silica sol is kept in a boiling state. After impregnation for 3 hours, the heating temperature is increased to 100°C, and the in-situ gel curing-drying is performed for 2 hours. Finally, the temperature is increased to 180°C and dried for 2 hours.
[0068] (3) After drying, the preform is taken out and the surface gel is cleaned and polished. The above operation is repeated twice to obtain a preform blank. The immersion time in the heating low-pressure boiling immersion process is reduced successively: the second immersion time is 2.5 h, and the third immersion time is 2 h. Subsequently, the blank is placed in a muffle furnace and heated to 750 °C at a heating rate of 2 °C / min and sintered for 150 min to obtain a composite material.
[0069] The quartz fiber reinforced quartz matrix composite material component prepared in this example was calculated by volume method, and the obtained sample volume density was 1.75 g / cm 3 , density blocks were taken from different parts of the component thickness direction for density testing, and the density fluctuation was ±0.03g / cm 3 After mechanical properties testing, the bending strength of the material is 106.2MPa, the bending modulus is 18.92GPa, and the mechanical properties are good.
[0070] The foregoing description of specific exemplary embodiments of the present invention is for the purpose of illustration and demonstration. These descriptions are not intended to limit the present invention to the precise form disclosed, and it is clear that many changes and variations can be made based on the above teachings. The purpose of selecting and describing the exemplary embodiments is to explain the specific principles of the present invention and its practical application, so that those skilled in the art can realize and utilize various different exemplary embodiments of the present invention and various different selections and changes. The scope of the present invention is intended to be limited by the claims and their equivalents.
Claims
1. A method for rapidly preparing a high-strength and high-density quartz fiber reinforced quartz-based composite material, characterized in that: The following steps are involved: (1) placing a quartz fiber preform that has been interface pretreated in a vacuum or inert atmosphere into a vacuum impregnation tank, adding silica sol to ensure that the preform is completely immersed, and sealing the impregnation tank; (2) Continuously heating the impregnation pot at low pressure to keep the silica sol in a violent boiling state at low pressure and low temperature, and performing low-pressure boiling impregnation. After a period of impregnation, the heating temperature is increased to perform in-situ gel curing of the silica sol, and low-pressure drying is performed. The low pressure state is maintained throughout the entire process to obtain a preform; (3) taking out the preform and cleaning the surface gel, and repeating the low-pressure boiling impregnation-in-situ gel curing-low-pressure drying process of step (2) several times, successively shortening the low-pressure boiling impregnation time during the cyclic impregnation process to obtain a preform; (4) Sintering the blank to obtain a high-strength and high-density quartz fiber reinforced quartz matrix composite material.
2. The method for rapidly preparing a high-strength and high-density quartz fiber reinforced quartz-based composite material according to claim 1, characterized in that: In the step (1), the interface pretreatment temperature of the quartz fiber preform is 400°C to 650°C, the heating rate is 1°C / min to 20°C / min, the insulation time is 60min to 360min, and the atmosphere during the pretreatment process is vacuum, nitrogen, helium or argon.
3. The method for rapidly preparing a high-strength and high-density quartz fiber reinforced quartz-based composite material according to claim 1, characterized in that: In the step (1), the impregnation tank is a contoured impregnation tank, which is contoured according to the outer dimensions of the fabric. After the silica sol is added, the silica sol liquid level is 10 mm to 80 mm higher than the top of the preform.
4. The method for rapidly preparing a high-strength and high-density quartz fiber reinforced quartz-based composite material according to claim 1, characterized in that: The silica sol is a high-purity stable acidic silica sol with a solid content of 20wt.% to 30wt.%, a viscosity of less than 15mpa·s, a pH of 2 to 4, and a SiO2 micelle particle size of 5nm to 100nm.
5. The method for rapidly preparing a high-strength and high-density quartz fiber reinforced quartz-based composite material according to claim 1, characterized in that: In the step (2), the air pressure in the tank is maintained at 500Pa to 1500Pa throughout the whole process, the low-pressure boiling immersion temperature is 5°C to 35°C, the immersion time is 0.5h to 3h, and the heating temperature is gradually increased during the in-situ gel curing and low-pressure drying process, the temperature range is 70°C to 250°C, and the gel curing time and low-pressure drying time are both 1h to 4h.
6. The method for rapidly preparing a high-strength and high-density quartz fiber reinforced quartz-based composite material according to claim 1, characterized in that: In the step (3), the low-pressure boiling impregnation-in-situ gel curing-low-pressure drying is circulated 1 to 6 times, the low-pressure boiling impregnation time decreases from the first vacuum impregnation time, and the in-situ gel curing and drying process system is the same as that of step (2).
7. The method for rapidly preparing a high-strength and high-density quartz fiber reinforced quartz-based composite material according to claim 6, characterized in that: The circulating low-pressure boiling immersion time is reduced by 0.2 to 1 hour.
8. The method for rapidly preparing a high-strength and high-density quartz fiber reinforced quartz-based composite material according to claim 1, characterized in that: In the step (4), sintering is carried out in a muffle furnace in air, the sintering temperature is 700° C. to 900° C., the heating rate is 1° C. / min to 10° C. / min, and the holding time is 30 min to 360 min.
9. A high-strength and high-density quartz fiber reinforced quartz-based composite material, characterized in that: The composite material is prepared by the method according to any one of claims 1 to 8.
Citation Information
Patent Citations
Preparation method for high-temperature-resistant ultra-thin antenna window
CN103601479A
Uniform compaction method of silicon oxide based antenna housing composite
CN105272119A
Quartz fiber reinforced quartz-based composite material and manufacturing method thereof
CN113511879A
High-density fiber-reinforced quartz ceramic composite material and preparation method thereof
CN113896554A
Preparation method of quartz fiber reinforced silicon dioxide antenna housing
CN117700251A